The impact of the bank-firm relations on the propagation of monetary policy squeezes: an empirical assessment for Italy - CONIGLIANI, C.; FERRI, G.; GENERALE, A. (PSL Quarterly Review, 2013)
The work analyses the bank-firm relationship in Italy, in order to verify its impact on the behaviour of banks towards customers and the effects on the transmission of monetary policy impulses. The authors single out a sub-group of borrowers whose dependence upon banks seems to be particularly close and examine banks’ behaviour towards this subgroup vis-a-vis other groups of firms. The analysis differs from previous empirical research in that a wider sample of non-financial firms is used, a stability index is employed among the explanatory variables, and the importance of customer relationships is tested with reference to the response of interest rates applied by banks during Italy’s sever episode of monetary restriction in 1992. Specifically, the work looks at the relation between the closeness of bank-firm relations and the probability of being rationed, the multiple borrowing of firms and the possibility that the recent consolidation of the banking system is bound to determine a strengthening in customer relationships. JEL Codes: G21